2005
DOI: 10.3171/jns.2005.103.2.0311
|View full text |Cite
|
Sign up to set email alerts
|

Surface properties, more than size, limiting convective distribution of virus-sized particles and viruses in the central nervous system

Abstract: These results indicate that convective distribution can be used to distribute therapeutic viral vectors in the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 30 publications
3
76
0
Order By: Relevance
“…Chen et al 46 and MacKay et al 47 demonstrated that polystyrene nanoparticles and liposomes with a diameter of 200 nm only penetrated short distances into the striatum of rats. Interestingly, however, Chen et al demonstrated that coating the nanoparticles with albumin to shield the hydrophobic particle surface significantly improved their distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 46 and MacKay et al 47 demonstrated that polystyrene nanoparticles and liposomes with a diameter of 200 nm only penetrated short distances into the striatum of rats. Interestingly, however, Chen et al demonstrated that coating the nanoparticles with albumin to shield the hydrophobic particle surface significantly improved their distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, Chen et al demonstrated that coating the nanoparticles with albumin to shield the hydrophobic particle surface significantly improved their distribution. 46 Furthermore, Neeves et al 48 demonstrated that preinfusing the striatum with isotonic saline significantly improved the distribution of 53 nm diameter polystyrene nanoparticles in the striatum of rats. This effect was greater than was observed with preinfusion of hyaluronidase to degrade the brain extracellular matrix or with hyperosmotic mannitol to osmotically expand the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…This study used MRI to follow the distribution of the MR contrast agent, Gd-DTPA. The range of tracers used in CED studies is wide, including small-molecular-weight compounds such as Gd-DTPA, 18,19,32 dendrimers, 21 iron oxides, 20,36 nanoparticles, 33 and viruses 5,32,33 with attached Gd moieties. The Gd-DTPA tracer is a small-molecularweight contrast agent with the widest FDA approval for use in CNS, body, and head and neck applications in both adults and children.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternative strategies have been developed for delivering nanoparticles to affected brain tissue. Intracranial infusion, or convection-enhanced delivery (CED), has been used to deliver low molecular weight molecules [2,25,1], proteins [24,23,26], and several kinds of particles, including liposomes [28,42,43,19,44,36] and polymeric nanoparticles [6]. Although small molecules and some proteins can be distributed throughout the brain with CED, it has proven difficult to distribute nanoparticles over comparable distances.…”
Section: Introductionmentioning
confidence: 99%